Harnessing the ethnomedicinal potential of Cassia fistula: Biogenic silver nanoparticles for DNA protection and cancer therapy - Mehul Chauhan; Priya Mori; Vijay Kumar; Khushal Kapadiya; Harison Masih; Swati Goswami (The Microbe)
This study investigates the total phenolic content, total flavonoid content, total tannin content, antioxidant properties, and antimicrobial activity of Cassia fistula fruit extracts, followed by the green synthesis of silver nanoparticles (AgNPs). The synthesized AgNPs were characterized for their physicochemical properties, including zeta potential, which was found to be −1.28 mV, indicating the stability of the nanoparticles in suspension. UV-Vis spectroscopy revealed a characteristic peak at 450 nm, confirming successful nanoparticle synthesis. High-resolution transmission electron microscopy (HR-TEM) and selected area electron diffraction (SAED) analyses showed the AgNPs exhibited diverse morphologies with an average diameter of 25.25 nm. Fourier transform infrared spectroscopy (FTIR) further confirmed the interaction between biomolecules and AgNPs through functional group analysis. The study also evaluated the DNA protection potential of the AgNPs against free radicals, demonstrating their ability to protect genetic material. Additionally, the AgNPs were tested on a panel of NCI-60 cell lines, revealing broad-spectrum anticancer activity. Notably, the AgNPs exhibited significant anticancer effects, with 85.47 % growth inhibition against renal (TK-10) and breast cancer (T-47D) cell lines, and a 15 % proliferative growth index. These findings highlight the potential of biogenic AgNPs from Cassia fistula as promising candidates for future biomedicine and cancer therapy applications.